Sensitivity of Staphylococcus aureus to antimicrobials used to treat bovine mastitis: review - Alves, Brenner; Chaves, Ana Júlia Silveira; Vieira, Natâne Flávia; Chaves, Glauco Vinício; França, Patrícia Maria de; Barezani, Amanda Soriano Araújo; Soares, Paulo Henrique Araújo (Pubvet, 2020)
Seen as one of the main economic and health problems in Brazilian properties, bovine mastitis shows as a disease of high prevalence among farm animals. One of the main bottlenecks related to this disease is antimicrobial resistance, especially when the etiology is associated with a Staphylococcus aureus bacterium. From this perspective, this paper aims to discuss the resistance profile of S. aureus and some factors involved. For this, the data were presented in the form of a narrative review of the literature, based on studies indexed as platforms: Portal of Journals CAPES-MEC and SciELO. An antimicrobial resistance profile of S. aureus was selected in the literature search, being the least used antibiotics in Penicillin and Ampicillin and the best use in the treatment of cephalothin. Other data compiled were that older animals are more likely to have antimicrobial resistance and that in some situations or the benefit of treatment of subclinical mastitis by S. aureus does not bring economic returns, but only in the quality to make milk. In this context, highlight the importance of new research to track the evolution of antimicrobial resistance of S. aureus, as well as promote extensive activities for education in the field on the correct therapeutic procedures of bovine mastitis.